Leveraging Religious Capital: Teacher Agency and Curriculum Reform in Indonesian Islamic Schools - Amalia, Eka Rizki (Pascasarjana Universitas KH. Abdul Chalim, 2025)
Curriculum transformation in Indonesian Islamic educational institutions (madrasahs) is essential in addressing globalization challenges and technology development. This research investigates the intersection of religious capital and teacher agency in these institutions, with the objective of understanding how Islamic values can shape curricular innovation without abandoning core Islamic educational principles. Systematic library-based research was employed to select the literature published in peer-reviewed publications from 2015 to the present using the following databases: Scopus, ERIC, IEEE Xplore, Web of Science, Google Scholar, JSTOR, ProQuest and ScienceDirect with the keywords listed to be included were,